2009
DOI: 10.1007/s10162-008-0154-7
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Nerve Fiber Responses to Combined Acoustic and Electric Stimulation

Abstract: Persons with a prosthesis implanted in a cochlea with residual acoustic sensitivity can, in some cases, achieve better speech perception with "hybrid" stimulation than with either acoustic or electric stimulation presented alone. Such improvements may involve "across auditory-nerve fiber" processes within central nuclei of the auditory system and within-fiber interactions at the level of the auditory nerve. Our study explored acoustic-electric interactions within feline auditory nerve fibers (ANFs) so as to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 25 publications
3
25
0
Order By: Relevance
“…This might be due to poststimulus inhibition of spontaneous activity typically found in the acoustically evoked auditory nerve response. Poststimulus phenomena after the offset of acoustic stimuli have also been described in a recent publication [Miller et al, 2009]. They used electric pulse trains and acoustic noise bursts as maskers and found that this reduced jitter in a postmasker interval (20 ms) dependent on the degree of spontaneous activity of the fibre, further supporting the influence of spontaneous activity on jitter and synchronization.…”
Section: Studies In Catsmentioning
confidence: 79%
“…This might be due to poststimulus inhibition of spontaneous activity typically found in the acoustically evoked auditory nerve response. Poststimulus phenomena after the offset of acoustic stimuli have also been described in a recent publication [Miller et al, 2009]. They used electric pulse trains and acoustic noise bursts as maskers and found that this reduced jitter in a postmasker interval (20 ms) dependent on the degree of spontaneous activity of the fibre, further supporting the influence of spontaneous activity on jitter and synchronization.…”
Section: Studies In Catsmentioning
confidence: 79%
“…Electrophysiologic animal studies provide evidence that electrophonic responses contribute to EAS responses 33 . Interactions between acoustic and ES are nonlinear in that neuronal spike rate will asymptote at the pulse rate of the electrical stimulus 34 . In most cases, increase in ES rate or level results in increased masking of the acoustic response in a predictable fashion, likely related to electrically evoked refractoriness, limiting the likelihood of “overdriving” the nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore a gradient of interaction exists such that acoustic stimuli of low frequency and high amplitude are less masked 35 . However, Miller et al report that in rare instances (4% of studied fibers), ES responses are “enhanced” by acoustic stimuli such that simultaneous presentation increases neuron spike activity above ES alone in a nonlinear fashion 34 . Stronks et al similarly cite the electrophonic response to explain nonlinear and delayed characteristics of combined electric/acoustic masking.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few studies that suggest that temporal sensitivity, such as that measured in strength-duration functions (threshold vs. phase duration), forwardmasking recovery, and multipulse integration functions (threshold vs. stimulation rate), benefits from broad stimulation of the cochlea (e.g., Brown et al 1996;Miller et al 2009;Smith and Finley 1997;Zhou and Dong 2017;Zhou and Pfingst 2016). Faster forward-masking recovery, steeper strength-duration functions, and greater multipulse integration were found in psychophysically estimated broader neural excitation patterns or when measured with MP relative to BP electrode configuration.…”
Section: Introductionmentioning
confidence: 99%